Changes of Intramuscular Fat Composition, Lipid Oxidation and Lipase Activity in Biceps femoris and Semimembranosus of Xuanwei Ham During Controlled Salting Stages - Zhen-yu WANG; Xiao-guang GAO; Ji-hong ZHANG; De-quan ZHANG; Chang-wei MA (Journal of Integrative Agriculture, 2013)
Fatty acid composition of neutral lipids (NLs), phospholipids (PLs) and free fatty acids (FFAs) from intramuscular fat (IMF), lipid oxidation and lipase activity in muscle Semimembranosus (SM) and msucle Biceps femoris (BF) of dry-cured Xuanwei ham during the 90-d salting stages were analysed. The salt content increased from 0.34 to 3.52% in BF and from 0.10 to 5.42% in SM during the 90 d salting stage, respectively. PLs of IMF in both BF and SM decreased 54.70% (P<0.001) and 34.64% (P<0.05), furthermore, the saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) of PLs in both muscles were hydrolysed almost isochronously. FFAs were increased from 0.46 g 100 g−1 lipids to 2.92 g 100 g−1 lipids in BF at the end of salting, which was lower than SM (from 1.29 g 100 g−1 lipids to 9.70 g 100 g−1 lipids). The activities of acid lipase, neutral lipase and acid phospholipase all remained active in the 90 d. The thiobarbituric acid reactive substances (TBARS) was slowly increased to 1.34 mg kg−1 muscle in BF and to 2.44 mg kg−1 muscle in SM during the salting stage. In conclusion, the controlled salting process prompted the hydrolysis of PLs of IMF notably and increased the lipid oxidation of muscles within some limits.